A clinician’s guide to recurrent isolated sleep paralysis - Sharpless, Brian A (Neuropsychiatr Dis Treat, 2016)
This review summarizes the empirical and clinical literature on sleep paralysis most relevant to practitioners. During episodes of sleep paralysis, the sufferer awakens to rapid eye movement sleep-based atonia combined with conscious awareness. This is usually a frightening event often accompanied by vivid, waking dreams (ie, hallucinations). When sleep paralysis occurs independently of narcolepsy and other medical conditions, it is termed “isolated” sleep paralysis. Although the more specific diagnostic syndrome of “recurrent isolated sleep paralysis” is a recognized sleep–wake disorder, it is not widely known to nonsleep specialists. This is likely due to the unusual nature of the condition, patient reluctance to disclose episodes for fear of embarrassment, and a lack of training during medical residencies and graduate education. In fact, a growing literature base has accrued on the prevalence, risk factors, and clinical impact of this condition, and a number of assessment instruments are currently available in both self-report and interview formats. After discussing these and providing suggestions for accurate diagnosis, differential diagnosis, and patient selection, the available treatment options are discussed. These consist of both pharmacological and psychotherapeutic interventions which, although promising, require more empirical support and larger, well-controlled trials.